An empirical analysis of vote buying among the poor: Evidence from elections in the Philippines - Canare, Tristan A (Archīum Ateneo, 2018)
Recent literature suggests that the poor are more likely to be targeted for vote buying and to sell their votes. However, there is limited empirical analysis on the patterns of vote buying among low-income voters. This paper attempts to fill this gap using a survey conducted in Metro Manila, Philippines after the 2016 elections. Data analysis shows that vote buying among the poor is indeed very common, but the incidence varies depending on the vote buying type. The most prevalent form uses more benign goods such as food and clothing, but offers of money is still reported by more than a quarter of respondents. Different vote-buying types also have different correlates, including some socio-economic factors, suggesting that it is a finely targeted activity. In addition, money vote buying is predominant in tight elections, but buying votes using non-monetary offers is more common when there is a clear winner even before the election. Most of those who were offered accepted the goods or money, but only about two-thirds voted for the candidate. In addition, evidence suggests that the good or money is not the deciding factor in voting for the candidate. This supports the premise that vote buying is just part of a bigger effort by politicians to build clientelism and patronage among his/her constituencies. Dependency and loyalty is merely punctuated by election-related transfers, rather than an effort to completely change votes.